Configuring Masculinity in Theory and Literary Practice - Horlacher, Stefan (DQR Studies in Literature, 2015)
Configuring Masculinity in Theory and Literary Practice combines a critical survey of the most important concepts in Masculinity Studies with a historical overview of how masculinity has been constructed within British Literature and a special focus on developments in the 20th and 21st centuries. Readership: This book is of key interest to students, university teachers, and researchers in the fields of British Literature, Gender, Masculinity, and Cultural Studies as well as Literary Studies generally.